ANALISIS KESIAPAN GURU DALAM MENERAPKAN PENDIDIKAN INKLUSI BAGI ANAK BERKEBUTUHAN KHUSUS - Neneng Sulasmi (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2025)
The prevalence of children with special needs in Indonesia is increasing, up to 10% of the total population of children. This means that about 10 out of every 100 children in Indonesia have special needs. The presence of children with special needs is a challenge in itself, which encourages all stakeholders to be able to formulate policies that favour the interests of children with special needs so that they get the same rights, especially in education as other children in general. Inclusion for all students is not just a hope, but an educational goal that must be achieved. The inclusion programme provides opportunities for children with special needs to receive education, optimise their potential and meet their learning needs, which in turn encourages the achievement of compulsory education targets. Teachers are one of the most important factors in the implementation of inclusive education, the success and achievement of education is highly dependent on the readiness of teachers as implementers of the inclusive education programme. This study aims to determine the readiness of teachers in implementing inclusive education, especially in schools. The research method used is literature review by filtering articles related to the time span 2018-2024. The results of the search for related journals were obtained as many as 8 journals which were analysed using thematic data techniques. The results of this study indicate that the readiness of teachers to implement inclusive education is still very low and unprepared. This is because teachers have no experience in teaching children with special needs. Teachers do not know the specific characteristics of children with special needs, besides that the ability of teachers is still very limited in terms of conducting assessments and identifying children's cases, developing learning programmes that suit children's needs, and the absence of training obtained by teachers to improve teachers' knowledge and abilities.